The Influence of Media-Based Learning Analog Clocks to Improve Understanding of Time Concept Students in Grade 2 of NU Metro Elementary School - Seyaningsih, Rika; Lutfi Fadilah (Journal of Research in Islamic Education, 2025)
This study aims to describe the effects of the use of analog clock-based educational learning media in improving the understanding of the concept of time in class II C students at SD NU Metro. This study shows that students' understanding of the concept of time, such as reading the clock and distinguishing between types of morning, afternoon, evening, and night, is still relatively low. This study uses a qualitative descriptive approach with data collection methods that include observation, interviews, and documentation studies. The subjects in this study include class teachers and 28 students from class II C. The study proves that the use of analog clock media helps students understand the concept of time in a more concrete way. Learning activities become more interactive, and students show high interest and enthusiasm in participating in learning. Teachers also feel helped in delivering material through the media. Thus, analog clock-based learning media has a good impact in helping students understand the concept of time optimally.